Customer Profitability Measurement Models: Their Merits and Sophistication across Contexts - Morten Holm (Copenhagen Business School (CBS), 2012)
The purpose of this dissertation is to expand our understanding of the applicability and performance effects of different Customer Profitability Measurement (CPM) models across contexts. Customer profitability measurement has attracted increasing interest recently – mainly in the marketing literature. The vast majority of this research has been case-based. Consequently, the evidence in this field consists of a number of case demonstrations indicating that using CPM models can be beneficial in specific industries but only very limited cross-sectional research investigating the general relationships between the CPM model use, context and firm financial performance. Researching these relationships is expected to contribute to marketing as well as management accounting literatures but also to managers working with or planning to start working with CPM models in practice for two reasons: First, marketing managers are increasingly required to be accountable for the marketing investments they expect to make. A better understanding of which CPM models that are applicable in different contexts will contribute to more efficient resource utilization in firms. Second, the management accounting literature on CPM models is very scarce despite the fact that this area is a key priority in practice. Knowledge on how CPM models are adapted to fit the environment in which the firm operates will contribute to our understanding of how CPM models should be designed but also to the general school of contingency-based management accounting research.
hdl:10398/8437
Keywords: 650